Hydrogen bonded organic framework material with ultra-high proton conductivity and preparation method and application thereof

By combining hydrogen bonded organic framework materials with Nafion to form a composite membrane, the problem of reduced proton conductivity of Nafion membrane under high or low temperature conditions is solved, and a composite membrane with high proton conductivity and stable performance is achieved, which promotes the commercial application of fuel cells.

CN116284826BActive Publication Date: 2025-03-25HENAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310270850.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-20
Publication Date
2025-03-25
Estimated Expiration
2043-03-20

AI Technical Summary

Technical Problem

The existing Nafion membranes will reduce proton conductivity under high or low temperature conditions, and most of the modified materials are hydrophilic materials, which will reduce proton conductivity, making it difficult to explore its proton conductivity and proton transport path.

Method used

A composite film is formed with a hydrogen bonded organic framework material [(CN5H8)(C10O8H5)] with ultra-high proton conductivity and Nafion, and a three-dimensional hydrogen bonded organic framework material is formed through hydrogen bonding, π-π stacking and van der Waals interaction.

Benefits of technology

The proton conductivity of the composite membrane is improved, stable performance under high and low temperature conditions is achieved, and it helps to explore the proton transport mechanism, promoting the large-scale commercial application of proton exchange membrane fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116284826B_ABST
    Figure CN116284826B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of fuel cell preparation, and discloses a hydrogen-bonded organic skeleton material with ultra-high proton conductivity. The structural formula of the hydrogen-bonded organic skeleton material is [(CN5H8)(C 10 O8H5)], each carboxylate anion C 10 8H5 ‒ With the adjacent carboxylate anion C 10 8H5 ‒ and 1,3‑diaminoguanidine cation CN5H8 + The two-dimensional layered structure is connected, and the two-dimensional layered structure is further expanded to form a three-dimensional hydrogen-bonded organic skeleton material. The proton conductivity of the composite membrane composed of the hydrogen-bonded organic skeleton material of the present invention is comparable to the proton conductivity of the commercial Nafion membrane, which is helpful to realize the large-scale commercial application of proton exchange membrane fuel cells, and the hydrogen-bonded organic skeleton material of the present invention is crystalline, which is conducive to exploring the proton transport mechanism of the proton exchange membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fuel cell preparation, and in particular relates to a hydrogen-bonded organic framework material with ultra-high proton conductivity, and a preparation method and application thereof. Background Art

[0002] Fuel cells directly convert renewable chemical energy into electrical energy, have high theoretical efficiency and power density, and are a very promising environmentally friendly power generation device. The current fuel cells mainly include: proton exchange membrane fuel cells (PEMFCs); phosphoric acid fuel cells (PAFCs); solid oxide fuel cells (SOFCs) and alkaline fuel cells (AFC). Among them, proton exchange membrane fuel cells are considered to be the most promising candidate to replace traditional energy due to their outstanding advantages such as green and high efficiency, ultra-low emissions, high power density, and fast startup speed. In proton exchange membrane fuel cells, the proton exchange membrane, as the core component of the entire system, needs to meet several conditions: high proton conductivity (>10 -2 Scm -1 ); good chemical and thermal stability; excellent gas barrier properties; good membrane (film) mechanical properties and processing properties; good compatibility with other components such as bipolar plates and electrode materials; low cost; easy to mass produce.

[0003] The first application in fuel cells was Nafion membrane produced by DuPont in 1960, which is a perfluorosulfonated polymer. It has excellent proton conductivity (10 -1 -10 -2 S cm -1 ), however, its temperature range of use has certain limitations. When the temperature is greater than 80°C or lower than -5°C, the proton conductivity will be destroyed. In addition, its high cost and complex synthesis process, as well as the existence of problems such as high-temperature water loss and excessive expansion, further limit its application. At present, the research on proton exchange membranes in proton exchange membrane fuel cells is mainly to improve proton conductivity and mechanical properties at high temperature and low humidity, including high-temperature proton exchange membranes, modified Nafion membranes and other new proton exchange membranes. At present, the recasting method is mainly used to develop composite membranes by adding hydrophilic fillers such as SiO2, TiO2, ZrO2, graphene oxide and functionalized polymers to modify Nafion membranes. However, since changes in chain structure or assembly environment will change the bicontinuous nanophase structure of Nafion membranes, thereby reducing their proton conductivity, the key to developing high-performance Nafion membranes is to simultaneously achieve high proton conductivity and excellent mechanical / chemical stability of Nafion membranes. In addition, as an amorphous material, it is difficult to explore the proton conduction behavior and proton transport path of Nafion membranes.

[0004] Hydrogen-bonded organic framework materials (HOFs), which are self-assembled from organic small molecule monomers through hydrogen bonding, π-π stacking and van der Waals interactions, are a new type of crystalline porous materials. With their large specific surface area, high porosity, low density, high adsorption and other properties, they have gradually become a powerful branch of porous organic framework materials (POPs). Compared with metal-organic frameworks (MOFs) formed by connecting inorganic metals and organic units, HOFs avoid metal nodes and have lower density and larger theoretical void volume. On the other hand, compared with covalent organic framework materials (COFs), the weak interactions involved in the assembly of HOFs are conducive to the formation of larger single crystals. Through single crystal X-ray diffraction structure analysis, detailed structural information of the compounds can be obtained, and more kinetic analysis can be performed. The preparation of hydrogen-bonded organic framework materials is very simple, avoiding tedious operational synthesis. At present, there are few reports on the use of hydrogen-bonded organic framework materials to modify Nafion membranes to improve their proton conductivity. Summary of the invention

[0005] The present invention aims to solve the technical problem that the modified materials of existing Nafion membranes are mostly hydrophilic materials, which will reduce the proton conductivity and be unfavorable for exploring the proton conduction behavior and proton transmission path thereof. The present invention provides a hydrogen-bonded organic skeleton material with ultra-high proton conductivity. The proton conductivity of the composite membrane formed by the hydrogen-bonded organic skeleton material and Nafion is relatively high, which is helpful to realize the large-scale commercial application of proton exchange membrane fuel cells. In addition, the crystalline hydrogen-bonded organic skeleton material is conducive to exploring the proton transmission mechanism of the proton exchange membrane.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a hydrogen-bonded organic framework material with ultra-high proton conductivity, wherein the structural formula of the hydrogen-bonded organic framework material is [(CN5H8)(C 10 O8H5)], each carboxylate anion C 10 8H5 - With the adjacent carboxylate anion C 10 8H5 - and 1,3-diaminoguanidine cation CN5H8 + The two-dimensional layered structure is connected to form a three-dimensional hydrogen-bonded organic framework material.

[0008] In one technical solution, the hydrogen-bonded organic framework material of the present invention belongs to the triclinic system, the P-1 space group, and the unit cell parameters are: α=89.173(7)°, β=88.911(6)°, γ=80.411(6)°.

[0009] In one technical solution, the three-dimensional structure of the hydrogen-bonded organic framework material of the present invention is specifically as follows: each carboxylate anion C 10 8H5 - Through the OH…O intermolecular hydrogen bonds with the adjacent carboxylate anion C 10 8H5 - , and through the intermolecular hydrogen bonds of NH…O with the 1,3-diaminoguanidine cation CN5H8 + The two-dimensional layered structure is connected to form a two-dimensional layered structure; the two-dimensional layered structure is further expanded through hydrogen bonds between NH…O molecules to form a three-dimensional hydrogen-bonded organic skeleton material.

[0010] In one technical solution, the hydrogen-bonded organic framework material of the present invention has adjacent carboxylate anions C along the a direction. 10 8H5 - There is a π-π stacking effect between the benzene rings in the and

[0011] The present invention also provides a method for preparing the above-mentioned hydrogen-bonded organic framework material with ultra-high proton conductivity, comprising the following steps: dissolving 1,2,4,5-benzenetetracarboxylic acid and 1,3-diaminoguanidine hydrochloride in methanol, slowly volatilizing at room temperature, filtering and drying to obtain colorless block crystals.

[0012] In one technical solution, the molar ratio of 1,2,4,5-benzenetetracarboxylic acid to 1,3-diaminoguanidine hydrochloride is 1:1.

[0013] The present invention also provides the use of the hydrogen-bonded organic skeleton material with ultra-high proton conductivity in preparing a proton exchange membrane for a fuel cell. The proton exchange membrane is a composite membrane formed by dispersing the hydrogen-bonded organic skeleton material in Nafion.

[0014] In one technical solution, the amount of hydrogen-bonded organic framework material added to the composite membrane is 100 to 110 mg.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] [(CN5H8)(C 10 O8H5)] compound powder proton conductivity at 358K and 98% RH reached 1.11×10 -2 S cm -1 The proton conductivity of the composite membrane composed of it and Nafion reaches 5.77×10 -2 S cm -1, which is higher than the proton conductivity of the existing Nafion membrane. This is mainly due to the synergistic effect of Nafion and the compound. In addition, the compound has simple synthesis conditions and high yield. Its stable three-dimensional framework structure helps to improve the mechanical stability of the Nafion membrane and help to achieve large-scale commercial application of proton exchange membrane fuel cells. In addition, the present invention studies that the proton transport mechanism of crystalline hydrogen-bonded organic skeleton materials follows a mixed mechanism of hopping and carrying, while the proton transport mechanism of the composite membrane follows a hopping mechanism. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 For the present invention [(CN5H8)(C 10 O8H5)] compound, wherein Figure 1 a is the asymmetric unit of the compound; Figure 1 b is the two-dimensional layer structure of the compound; Figure 1 c is the three-dimensional structure of the compound, Figure 1 d is the topological simplified structure of the compound.

[0018] Figure 2 For the present invention [[(CN5H8)(C 10 PXRD spectra of [O8H5)] compounds at different humidity.

[0019] Figure 3 For the present invention [(CN5H8)(C 10 O8H5)] compound powder proton conductivity test results, among which, Figure 3 a is the Nyquist plot at different relative humidity at 298K; Figure 3 b is the Nyquist plot at different temperatures at 98% RH; Figure 3 c is ln(σT) vs 1000T -1 curve; Figure 3 d PXRD patterns before and after proton conductivity test.

[0020] Figure 4 is the characterization result of the proton exchange composite membrane of the present invention, wherein, Figure 4 a is a picture of the composite film; Figure 4 b is the SEM image of the composite membrane; Figure 4 c is the infrared spectrum of the composite film; Figure 4 d is the XRD spectrum of the composite film.

[0021] Figure 5 The proton conductivity test results of the proton exchange composite membrane of the present invention are as follows: Figure 5 a is the Nyquist plot at different relative humidity at 298K; Figure 5 b is the Nyquist plot at different temperatures at 98% RH; Figure 5 c is ln(σT) vs 1000T -1 curve; Figure 5 d is the comparison of proton conductivity of the composite membrane and the Nafion membrane used at different temperatures when 98% RH. DETAILED DESCRIPTION

[0022] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. The test methods in the following examples are conventional methods unless otherwise specified.

[0023] Example 1 Preparation and characterization of hydrogen-bonded organic framework materials

[0024] 1,2,4,5-benzenetetracarboxylic acid (0.2 mmol, 0.05 g) and 1,3-diaminoguanidine hydrochloride (0.2 mmol, 0.025 g) were dissolved in 4 mL of methanol, and the mixed solution was slowly evaporated at room temperature, filtered and dried to obtain colorless block crystals (yield: 56.1%, calculated based on 1,2,4,5-benzenetetracarboxylic acid).

[0025] 1) Elemental analysis (%): Theoretical value: C 38.49, N 20.40, H 3.82, calculated value: C 38.32, N 20.63, H3.80.

[0026] 2) Infrared spectrum data (KBr, cm -1 ):3444(m),3383(w),3362(w),3317(m),2777(w),2611(w),2490(w),1678(s),1 590(m),1447(m),1281(s),1121(m),1016(m),806(m),762(m),658(m),558(m). Among them: C 10 O8H6(1,2,4,5-benzenetetracarboxylic acid), CN5H8Cl(1,3-diaminoguanidine hydrochloride).

[0027] 3) Crystal structure characterization

[0028] Single crystals of suitable size were selected for X-ray diffraction analysis on ROD, Synergy Custom system, HyPix diffractometer, and the test temperature was 213 (2) K. GaKα radiation was used. The crystal diffraction point data were collected and the data were restored and absorption corrected by the direct method. The structure was analyzed and refined by the SHELXS-2014 and SHELXL-2014 programs. The coordinates of non-hydrogen atoms in the structure were corrected for anisotropic temperature factors using the full matrix least squares method, and the coordinates of hydrogen atoms were obtained by the difference Fourier synthesis method. The crystallographic data of the compound are shown in Table 1.

[0029] Table 1 [(CN5H8)(C 10 Crystallographic data of the compound

[0030]

[0031]

[0032] X-ray single crystal diffraction results show that the compound crystallizes in the triclinic system, P-1 space group, and the entire structure is a three-dimensional network constructed by hydrogen bonds. Figure 1 As shown in a, the asymmetric unit of the compound contains a 1,3-diaminoguanidine cation CN5H8 + and a carboxylate anion C 10 8H5 - , in C 10 8H5 - There is an intramolecular hydrogen bond O3-H3C…O2 between the carboxyl groups. Each carboxylate anion C 10 8H5 - Through various OH…O intermolecular hydrogen bonds with neighboring C 10 8H5 - And the hydrogen bond between NH…O molecules and 1,3-diaminoguanidine cation CN5H8 + Connect to form a two-dimensional layered structure (such as Figure 1 In addition, the two-dimensional interlayer is further extended into a three-dimensional hydrogen bond skeleton structure through hydrogen bonds between NH…O molecules (as shown in Figure 1 c), while, along the direction a, the adjacent carboxylate anion C 10 8H5 - There is also a π-π stacking effect between the benzene rings in the and This supramolecular effect is beneficial to increase the stability of the three-dimensional structure of the compound.

[0033] From the perspective of topology, the hydrogen bond network in this compound is analyzed. 10 8H5 - and 1,3-diaminoguanidine cation CN5H8 + can be viewed as 10-connection points and 6-connection points respectively, then the entire three-dimensional skeleton will be simplified into a two-node topology, and the topological symbol is {32 .4 9 .5 4}{3 4 .4 16 .5 15 .6 10},like Figure 1 As shown in d.

[0034] 4) The X-ray powder diffraction (PXRD) spectra of the compound at a series of different humidity levels were consistent with the theoretical values ​​obtained by X-ray single crystal diffraction (see Figure 2 ), indicating that the compound has good stability under different humidity conditions.

[0035] 5)[(CN5H8)(C 10 Powder proton conductivity test of [O8H5)] compounds

[0036] The crystals of the compound were ground into powder, and a certain mass of the powder sample was placed on a tablet press mold with a diameter of 3 mm. It was pressed for about two minutes using a pressure of 0.5 MPa to obtain a disc with a diameter of 0.052 mm. Conductive silver glue was evenly applied on the upper and lower sections of the disc, and it was fixed on the sample stage with gold wire for testing. The instrument used for the alternating current impedance (AC) test of the compound was a high-precision impedance gain phase analyzer (Solartron 1260 / 1296). The measured frequency range was 0.01 to 10 MHz, the input voltage was 100 mV, the measured temperature range was from 298 K to 358 K, and the humidity range was from 55% RH to 98% RH. Conductivity σ (S cm -1 ) is calculated by the formula σ = L / (RA), where L (cm) and A (cm 2 ) represent the thickness and cross-sectional area of ​​the disc, respectively, and R (Ω) is the resistance value of the sample, which is obtained by simulating the impedance data in the Nyquist diagram using the Zview equivalent circuit method. The conductivity of the compound is calculated from the resistance in the Nyquist diagram. a ) Through the Arrhenius formula σT=σ o exp(-E a / kT), where k is the Boltzmann constant (eV / k) and T (K) is the temperature.

[0037] like Figure 3 As shown in a, at 298K, as the relative humidity increases from 55% to 98%, the conductivity of the compound increases continuously, from 5.75×10 -10 S cm -1 to 9.20×10 -4 S cm -1 , increased by six orders of magnitude, indicating that humidity has a great influence on the test of proton conductivity. Figure 3 As shown in Fig. 2b, when the relative humidity is 98% and the temperature is continuously increased to 358K, the proton conductivity of the compound reaches 1.11×10 -2 S cm -1 , surpassing most of the reported metal-organic framework materials and hydrogen-bonded organic framework materials, and is a proton conductive material with great application prospects.

[0038] In order to further explore the proton transport mechanism, the Arrhenius equation was used to fit the temperature-dependent proton conductivity, and [ln(σT) vs 1000T -1 ] Drawing (see Figure 3 c) Calculate the activation energy E of the compound a It is 0.47eV, following a mixed mechanism of hopping and carrying.

[0039] In addition, the samples after proton conductivity test were tested by X-ray powder diffraction (XRD), such as Figure 3 As shown in Figure d, the position of the peak in the XRD spectrum is basically consistent with the theoretical peak of the XRD spectrum obtained by single crystal data simulation, indicating that the structure of the compound has not changed after the test.

[0040] Example 2 Preparation and Characterization of Proton Exchange Composite Membrane

[0041] 2mL of 5wt% Nafion solution (from DuPont Nafion membrane solution D520) was evaporated and concentrated to 1mL at 50℃, then 2mL of DMF was added and evaporated and concentrated to 1.5mL at 60℃. Subsequently, 0.1g of the compound ground into powder was evenly dispersed in 1.5mL of the mixture, stirred for 3h, transferred to an evaporating dish with a diameter of 35mm, and placed in a vacuum drying oven at 60℃ to obtain a composite membrane. The composite membrane was boiled in a 3wt% H2O2 solution, then immersed in a 1mol / L H2SO4 solution, then washed with distilled water and dried at room temperature. The content of the compound in the composite membrane is 53%. The appearance picture of the composite membrane is as follows Figure 4 As shown in a.

[0042] The composite membrane was tested by scanning electron microscopy (SEM). Figure 4 As shown in b, it can be seen from the figure that the surface of the composite membrane is smooth, indicating that the compound is uniformly dispersed in the Nafion solution.

[0043] In addition, potassium bromide tableting method is used at 400-4000cm -1 The infrared spectra of the compounds and composite films were tested in the range of 1.17 W using a Bruker VERTEX-70 Fourier transform infrared spectrometer. Figure 4As shown in c, the composite membrane shows infrared characteristic peaks of the compound and Nafion, indicating that the composite membrane was successfully prepared. Similarly, the XRD spectra of the compound and the composite membrane (such as Figure 4 d), 2θ=17° represents the characteristic peak of Nafion, which further illustrates the successful preparation of the composite membrane.

[0044] As mentioned above, the powder sample of the compound has a very high proton conductivity under the conditions of 358K and 98% RH. In order to study its application performance, a proton conductivity test was conducted on the composite membrane. The size of the composite membrane used for the test was: length × width = 10mm × 3mm. The test method was the same as in Example 1. Figure 5 As shown in a, the proton conductivity of the composite membrane at 298K and 55% RH is 1.16×10 -8 S cm -1 As the relative humidity increases, the proton conductivity reaches 3.29×10 -3 S cm -1 , increased by five orders of magnitude. Figure 5 As shown in b, under 98% RH, when the temperature rises to 358K, the proton conductivity of the composite reaches 5.77×10 -2 S cm -1 , which is higher than the proton conductivity of the Nafion membrane used ( Figure 5 d) The activation energy E of the composite film was obtained by fitting the Arrhenius formula a is 0.30eV (such as Figure 5 c), it follows the jumping mechanism.

[0045] The embodiments described above are only preferred embodiments of the present invention and are only used to explain the present invention, not to limit the scope of implementation of the present invention. For those skilled in the art, other implementation methods can certainly be easily made by replacement or modification based on the technical contents disclosed in this specification. Therefore, all changes and improvements made on the principles of the present invention should be included in the scope of the patent application of the present invention.

Claims

1. A hydrogen-bonded organic framework material with ultra-high proton conductivity, characterized in that: The structural formula of the hydrogen bond organic framework material is [(CN5H8)(C 10 O8H5)], each carboxylate anion C 10 8H5 - With the adjacent carboxylate anion C 10 8H5 - and 1,3-diaminoguanidine cation CN5H8 + The two-dimensional layered structure is further extended to form a three-dimensional hydrogen bonded organic framework material. 10 8H5 - It is the anion of 1,2,4,5-benzenetetracarboxylic acid.

2. The hydrogen-bonded organic framework material according to claim 1, characterized in that The hydrogen-bonded organic framework material belongs to the triclinic system, the P-1 space group, and the unit cell parameters are: α=89.173(7)°, β=88.911(6)°, γ=80.411(6)°.

3. The hydrogen-bonded organic framework material according to claim 1, characterized in that The three-dimensional structure of the hydrogen-bonded organic framework material is as follows: each carboxylate anion C 10 8H5 - Through the OH…O intermolecular hydrogen bonds with the adjacent carboxylate anion C 10 8H5 - , and through the intermolecular hydrogen bonds of NH…O with the 1,3-diaminoguanidine cation CN5H8 + The two-dimensional layered structure is connected to form a two-dimensional layered structure; the two-dimensional layered structure is further expanded through hydrogen bonds between NH…O molecules to form a three-dimensional hydrogen-bonded organic skeleton material.

4. The hydrogen-bonded organic framework material according to claim 1, characterized in that The hydrogen bonded organic framework material is along the a direction, and the adjacent carboxylate anion C 10 8H5 - There is a π-π stacking effect between the benzene rings in the and 5. The method for preparing a hydrogen-bonded organic framework material with ultra-high proton conductivity according to claim 1, characterized in that: The following steps are involved: 1,2,4,5-benzenetetracarboxylic acid and 1,3-diaminoguanidine hydrochloride were dissolved in methanol, slowly evaporated at room temperature, filtered and dried to obtain colorless block crystals.

6. The method for preparing a hydrogen-bonded organic framework material with high superproton conductivity according to claim 5, characterized in that: The molar ratio of the 1,2,4,5-benzenetetracarboxylic acid to the 1,3-diaminoguanidine hydrochloride is 1:

1.

7. Use of the hydrogen-bonded organic framework material with ultra-high proton conductivity according to any one of claims 1 to 4 in the preparation of a proton exchange membrane for a fuel cell, characterized in that: The proton exchange membrane is a composite membrane formed by dispersing the hydrogen bond organic framework material in Nafion.

8. The use according to claim 7, characterized in that: The added amount of the hydrogen-bonded organic framework material in the composite membrane is 100-110 mg.